Corporate social performance in the age of irresponsibility : cross national perspective - Stachowicz-Stanusch, Agata (Contemporary perspectives in corporate social performance and policy (Series), 2016)
Corporate Social Performance In The Age Of Irresponsibility - Cross National Perspective is authored by a range of international experts with a diversity of backgrounds and perspectives and provides a collection of ideas, examples and solutions on CSP implementation in the time of irresponsibility. Although Corporate Social Performance (CSP) has become important part of the management agenda of many enterprises and many companies adding socially responsible statements to their websites and mission statements some firms behave irresponsibly while at the same time acting positively on some dimensions-- 'corporate social irresponsibility (CSI) and responsibility can exist at the same time in the same firm.' (Gonzalez-Perez, 2011).This volume is aimed at presenting Corporate Social Performance concept from distinct cultural perspectives with the reference to responsible and irresponsible practices of various entities from different parts of the world.